The mediating role of teacher’s effective feedback in the relationship between teaching methods and students’ achievement motivation, Islamic Azad University, Islamshahr branch - Gholizadeh, Hamid; Zabihi, Rozita; Mirzamani, Seyed Mahmoud (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2021)
Background and purpose: teacher’s feedback can have an impact on students’ academic activities outside the academic environment and can have an effective role in motivating academic progress. Therefore, the present study aimed to investigate the mediating role of the practical feedback of the professor in the relationship between teaching methods and the motivation of the students of Islamic Azad University, Islamshahr branch. Methodology: The current research was a correlational descriptive study. The statistical population of the current research was all the professors and students of Islamic Azad University, Islamshahr branch, in the academic year 2015-2016. Based on Morgan’s table, the statistical sample included 377 students, and 302 professors were selected using the available sampling method. In this research, students answered questionnaires about effective feedback and improvement motivation, and professors answered questionnaires about teaching methods. The collected data were analyzed using Pearson’s correlation coefficients, regression, and path analysis. Results: The analysis of the results showed a significant relationship between feedback type, feedback structure, and feedback time with all five teaching styles and motivation to progress, and the components of feedback type, feedback structure, and feedback time could predict motivation to progress. Also, specialized teaching style, formal authority teaching style, and personal model teaching style were able to predict career motivation in students. Conclusion: The results showed that in the path analysis, the direct effect of feedback type, feedback structure, and feedback time, as well as expert style, authority style, interactive style, personal style, and facilitative style, on the motivation to progress was significant at the level of 0.01.